2000
DOI: 10.2355/isijinternational.40.519
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanism of Ductile Crack Initiation in Structural Steels Based on Void Nucleation and Growth.

Abstract: The effect of the specimen geometry and the inclusion content on the critical condition for ductile crack initiation was determined using notched round bar tensile specimens, and the critical void volume fraction and secondary void nucleation effect were investigated using the Gurson-Tvergaard constitutive model. It is shown that the secondary void nucleation from pearlite nodules plays a dominant role in ductile crack initiation, and void nucleation and void growth behavior are strongly affected by the stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Zhang and Niemi 32) investigated the critical void volume fraction under various triaxial stress states based on the Thomason's plastic limit-load criterion 33) combined with the G-T model for determining void growth behavior, and showed that the critical void volume fraction for materials with relatively large initial void volume fraction, f 0 , is affected by stress triaxiality, while f c is almost constant for materials with small values of f 0 . Ishikawa et al 17) also suggested a constant critical void volume fraction for steels with a small MnS content by comparing experimental investigations and calculation using the G-T model.…”
Section: Effect Of Stress Triaxiality On Critical Void Volume Fractiomentioning
confidence: 99%
See 4 more Smart Citations
“…Zhang and Niemi 32) investigated the critical void volume fraction under various triaxial stress states based on the Thomason's plastic limit-load criterion 33) combined with the G-T model for determining void growth behavior, and showed that the critical void volume fraction for materials with relatively large initial void volume fraction, f 0 , is affected by stress triaxiality, while f c is almost constant for materials with small values of f 0 . Ishikawa et al 17) also suggested a constant critical void volume fraction for steels with a small MnS content by comparing experimental investigations and calculation using the G-T model.…”
Section: Effect Of Stress Triaxiality On Critical Void Volume Fractiomentioning
confidence: 99%
“…However, ductile cracking in relatively clean ferrite-pearlite steels is dominated by secondary void nucleation from pearlite nodules. 17) Therefore, a characteristic length for ductile cracking is related to the mean spacing of pearlite nodules, as illustrated in Fig. 11.…”
Section: Fe Analysis Of Ductilementioning
confidence: 99%
See 3 more Smart Citations